An introduction to statistical concepts - Debbie L. Hahs-Vaughn and Richard G. Lomax (New York, NY Routledge, Taylor & Francis Group, 2020)
Introduction -- Data representation -- Univariate population parameters and sample statistics -- The normal distribution and standard scores -- Introduction to probability and sample statistics -- Introduction to hypothesis testing : inferences about a single mean -- Inferences about the difference between two means -- Inferences about proportions -- Inferences about variances -- Bivariate measures of association -- One-factor analysis of variance : fixed-effects model -- Multiple comparison procedures -- Factorial analysis of variance : fixed-effects model -- Introduction to analysis of covariance : the one-factor fixed-effects model with a single covariate -- Random- and mixed-effects analysis of variance models -- Hierarchical and randomized block analysis of variance models -- Simple linear regression -- Multiple linear regression -- Logistic regression -- Mediation and moderation.
Includes bibliographical references and indexes
Keywords: Statistics--Textbooks